Use of gas chromatography–mass spectrometry for definitive diagnosis of synthetic cannabinoid toxicity in a dog. Issue 5 (24th July 2019) - Kelmer, Efrat; Shimshoni, Jakob A.; Merbl, Yael; Kolski, Ofer; Klainbart, Sigal
Abstract: Objective: To report the use of gas chromatography–mass spectrometry to confirm a diagnosis of synthetic cannabis toxicosis in a dog and to describe the clinical course of the intoxication. Case Summary: An 11‐year‐old neutered female Boxer dog was referred due to acute onset of vomiting, ataxia, dull mentation, and delirium that progressed to generalized seizures, unresponsive to diazepam. Prior to presentation, the dog was found lying down, minimally responsive with vomitus around it. A chewed bag containing dried plant material was found next to the dog. The dog was anesthetized and ventilated with positive pressure for 16 hours, and eventually made a full recovery. Gas chromatography–mass spectrometry analysis of the plant material and a plasma sample from the dog revealed presence of the synthetic cannabinoid N ‐[(1 S )‐1‐(aminocarbonyl)‐2‐methylpropyl]‐1‐(cyclohexylmethyl)‐1 H ‐indazole‐3‐carboxamide, also known as AB‐CHMINACA, a relatively new illegal synthetic cannabinoid, known by the local forensic police department as a drug of recreational abuse. New or Unique Information Provided: Reports of synthetic cannabinoid toxicosis in dogs are scarce and are based on urine test kits for tetrahydrocannabinol that have not been validated in the veterinary literature. This is the first report to describe utilization of gas chromatography–mass spectrometry on canine plasma to reach a definitive diagnosis.